Spray-dried Spirulina platensis as an effective ingredient to improve yogurt formulations: Testing different encapsulating solutions. (September 2019) - da Silva, Samara C.; Fernandes, Isabel P.; Barros, Lillian; Fernandes, Ângela; José Alves, Maria; Calhelha, Ricardo C.; Pereira, Carla; Barreira, João C.M.; Manrique, Yaidelin; Colla, E.; Ferreira, Isabel C.F.R.; Filomena Barreiro, M.
Graphical abstract: Highlights: Improved spirulina-based ingredients were produced by spray-drying. Maltodextrin and maltodextrin crosslinked with citric acid were used. The novel ingredients offer advantages over the direct use of spirulina. The best solution is based on maltodextrin crosslinked with citric acid. Abstract: The consumption of foods functionalized with spirulina might have positive health effects. However, spirulina-based food products are usually associated with unpleasant flavor and odor, and can present non-homogeneous appearance, impairing consumers' acceptance. Moreover, it is important to assure bioactivity maintenance. To develop a novel food ingredient, spirulina was chemically characterized, and spray-dried using two encapsulating materials: i) maltodextrin and ii) maltodextrin crosslinked with citric acid. Thereafter, free and encapsulated spirulina were evaluated for their bioactive properties. Microencapsulated spirulina presented higher thermal stability than the base materials, while showing better anti-inflammatory activity without exerting cytotoxicity. Free and encapsulated spirulina were further added to yogurts to validate their suitability as functionalizing agents. Yogurts added with encapsulated spirulina presented a more homogeneous appearance, and the best solution was spirulina encapsulated in maltodextrin crosslinked with citric acid, considering the nutritional profile, attractive color, and improved antioxidant activity throughout storage time.